Gastrointestinal parasitism by helminths and protozoa in wild birds rescued from trafficking in riverside communities on the são francisco river, sergipe, Brazil - dos Santos, Anna Luiza Hora (2024)
Illegal wildlife trafficking is a practice that represents a significant threat to biodiversity and public health in many regions of the world. Birds that are victims of trafficking are subjected to conditions of stress and confinement that favor the proliferation of parasites, compromising animal health and well-being. Furthermore, some of these parasites have zoonotic potential, posing an additional risk to human health. Therefore, this study aims to identify the gastrointestinal parasites present in wild birds originating from trafficking in the São Francisco River Basin region, providing important information about the risks to bird health and human health. Fecal samples were collected from wild birds (n=80) belonging to the orders Passeriformes, Columbiformes, and Psitaciformes. The samples were analyzed using two parasitological techniques: Mini – FLOTAC© and centrifugal-sedimentation with Ziehl-Neelsen staining, to identify the presence of gastrointestinal parasites. The results indicate a prevalence of helminths, such as Capillaria sp. (1.5%) and Trichostrongylidae (32.8%), and protozoa, such as Eimeria sp. (5%), Isospora sp. (53,7%), Cryptosporidium sp. (83.7) and Entamoeba sp. (44.8%). Furthermore, these parasites compromise animal health and well-being, causing clinical signs such as diarrhea, loss of appetite, weight loss, and death. In short, the identification of gastrointestinal parasites in wild birds rescued from trafficking in riverside communities is essential to understanding the risks to bird health and public health in the region.